Kalabu (Kalamansi and Purple Sweet Potato) Snack Bar Innovation as an Alternative Snack for Diabetes - Ismiati; Patroni, Rini; Andeka Marleni, Wisuda; Febryanti, Ade (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2024)
Diabetes mellitus (DM) is a metabolic health disorder characterized by high blood sugar levels (hyperglycemia). Factors that can cause diabetes are heredity and an unhealthy lifestyle. The innovation of healthy snack bar 'Kalabu' aims to support the Healthy Living Community Movement (GERMAS). Snack bar "Kalabu" is a food product made from a mixture of local food ingredients kalamansi orange and purple sweet potato, then formed into a solid and compact form (food bar form). Product selection is based on current trends in society, is a practical alternative snack that can be consumed between activities and can be used to delay hunger when facing rush hours at certain times. This activity was carried out in Anggut Atas Village involving 5 alumni and 20 small business owners using demonstration and evaluation methods. Data analysis on knowledge was carried out using the T-Test test. The results of the implementation of community service obtained that the average knowledge of mothers about DM increased from 80.40 to 94.60. Likewise, with the acceptance of kalabu snack bar, most mothers (50%) liked the combination of purple sweet potato and kalamansi orange, and only a small percentage (15%) did not like the combination of kalabu snack bar flavors. It is expected to be an alternative to healthy snacks in an effort to support the healthy living community movement (GERMAS), especially as an alternative snack food that is safe for diabetics.